A Daily Diary Study on the Consequences of Networking on Employees' Career-Related Outcomes: The Mediating Role of Positive Affect - Volmer, Judith; Wolff, Hans-Georg (Frontiers in Psychology, 2018)
Although researchers have shown that networking is positively associated with numerous long-term outcomes (e.g., salary, promotion) an investigation of proximal outcomes of networking is still missing. Building on Conservation of Resources theory (COR; Hobfoll, 2001; Hobfoll, 2011) and conducting a daily diary study over five consecutive working days (N = 160 academics), we investigated short-term effects of networking on employees’ career-related outcomes (i.e., career optimism and career satisfaction), job attitudes (i.e., job satisfaction) and well-being (i.e., emotional exhaustion). Further, we suggested that positive affect would act as a mediator. Results from hierarchical linear modeling (HLM) showed that daily networking relates to all four outcome variables. Moreover, positive affect mediated three of four hypothesized relationships, with a marginally significant effect for career satisfaction. By providing evidence for valuable short-term benefits of networking, our study extends existing research on positive long-term effects (for example on salary, promotions). Findings broaden the scope by integrating networking research with a positive organizational behavior perspective. We discuss practical implications with regard to career intervention strategies, study limitations, and prospects for future research.